Perencanaan Penanggulangan Keadaan Darurat Transportasi Darat Bahan Kimia Butadien Rute Bojonegara - Cengkareng pada PT X Indonesia - Roza, Nelvy; Lestari, Fatma (UI Scholars Hub, 2010)
PT X Indonesia mentransport butadien dari terminal penimbunan di Bojonegara ke pengolahan di Cengkareng. Penelitian ini bertujuan mengidentifikasi potensi bahaya, memprediksi risiko, dan mengevaluasi prosedur penanggulangan keadaan darurat. Sampel diambil di salah satu rute perjalanan Bojonegara - Cengkareng. Data diperoleh dari observasi, wawancara, catatan, pelaporan dan prosedur penanggulangan keadaan darurat. Rencana penanggulangan keadaan darurat dianalisis secara kualitatif dengan membandingkan PT X Indonesia dengan standar Manitoba Industrial Accidents Council dan Advisory Committee on the Transport of Dangerous Goods - Prosedur penanggulangan keadaan darurat meliputi kebijakan perusahaan, analisa risiko, organisasi, sarana dan prasarana, tindakan penanggulangan serta pelatihan dan simulasi. Hasil penelitian menunjukkan perusahaan telah menetapkan prosedur tindakan keadaan darurat yang sudah dikaji, direvisi dan didistribusikan kepada semua personil terlibat. Risiko diidentifikasi berdasarkan penelusuran Material Safety Data Sheet dan Transport Emergency Card. Perusahaan menetapkan tim tanggap darurat dengan program pencegahan antara lain pemeriksaan kendaraan sebelum berangkat, penentuan kualifikasi pengemudi, dan kondisi kendaraan. Perusahaan menyediakan peralatan keadaan darurat seperti pemadam kebakaran, safety shoes, helm, dan sarung tangan, membekali pengemudi pengetahuan tindakan dalam keadaan darurat. Pelatihan dan simulasi perlu ditingkatkan khususnya penanggulangan keadaan darurat angkutan butadien. PT X Indonesia transports butadiene from its storage terminal in Bojonegara to processing plant in Cengkareng. This research identified potential hazard during butadiene transport, evaluate risk, and evaluate the emergency response preparedness during butadiene transport. Sample is taken from one route from Bojonegara to Cengkareng and data were obtained from observation, interview, records, reports and emergency response preparedness procedure. Qualitative and comparative analysis was conducted between existing emergency response procedures at PT X Indonesia with Manitoba Industrial Accidents Council Standards and Advisory Committee on the Transport of Dangerous Goods - Australia. Elements analysed including company policy, risk analysis, organization, facilities and equipment, emergency response steps, training and emergency drill. Results suggested that company’s policy has been set up for emergency response procedure and has been reviewed, revised, and distributed to all related parties. Risk analysis conducted using hazard identification method by reviewing Material Safety Data Saheet and Transport Emergency Card to determine butadiene toxicity, carcinogenicity, and flammability. Consequences analysis was conducted based on worst case scenario of Boiling Liquid Expanding Vapour Explosion. Emergency Response Preparedness organization was established. Accident prevention was also implemented such as tank inspection, driver’s qualification, and tank condition inspection. Emergency response equipment and facilities included fire extinguishers, safety shoes, helm, and gloves that included emergency steps, knowledge to the driver regarding emergency response . Emergency drill element should be improved, as existing drill not specific for butadiene transport emergency response.